AIR MENGALIR TIDAK SAMPAI JAUH: KONFLIK SUMBER DAYA AIR DI BOYALALI JAWA TENGAH - Harsasto, Priyatno (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2006)
In addition to physical destruction, societies emerging from conflict faced an erosion of social capital, understood as the basis for joint community actions and the social cohesion that needs to underpin a country-owned development effort. Based on an increasing focus on participatory and community-based approaches, there will be a need to better understand the linkages and potential between conflict and community-driven development. There was need to rebuild communities and their social capital from the bottom which acknowledges that local communities possess the core skills, incentives and organizational capacity to decide on and imple-ment a large number of development projects.